The Rigidity of Exhaustion: A Correlational Study Between Teacher Burnout and Observed Pedagogical Flexibility - Kiani, Sadiqa; Saleem, Shazia; Akhtar, Humair (The Knowledge, 2026)
Teacher burnout is a well-documented issue that is becoming widespread in modern education, yet its effects on manifested classroom behavior have not been properly studied. The present research examined the connection between teacher burnout and pedagogical flexibility in classroom teaching in terms of the ability to adjust the process of teaching and respond to the needs of learners and contextual requirements. The correlational research design was used to gather data of 300 secondary school teachers in District Haripur. Teacher burnout was assessed using the Maslach Burnout Inventory, which included emotional exhaustion, depersonalization and diminished personal accomplishment whereas pedagogical flexibility was measured through a structured classroom observation tool that comprised of several facets of adaptive instruction. The results of descriptive statistics showed that the level of emotional exhaustion among teachers is moderate to high, the level of depersonalization is lower, and the variability of observed pedagogical flexibility is limited. Pearson correlation showed emotional exhaustion had a moderate negative relationship with pedagogical flexibility, while depersonalization had a significant negative relationship with responsive instructional behaviors. Reduced personal accomplishment was positively related to instructional adaptation. Multiple regression confirmed emotional exhaustion as a significant negative predictor of composite.The strength of the regression model was verified through the assumption testing. The results indicate that burnout, and in particular, emotional exhaustion is reflected in instructional rigidity which limits teachers to adaptive and responsive pedagogy. The article highlights the necessity of considering teacher well-being as a factor leading to maintaining pedagogical agility and teaching standards.